Assessment of nursing students' competence in clinical practice: A systematic review of reviews. (December 2019) - Immonen, Kati; Oikarainen, Ashlee; Tomietto, Marco; Kääriäinen, Maria; Tuomikoski, Anna-Maria; Kaučič, Boris Miha; Filej, Bojana; Riklikiene, Olga; Flores Vizcaya-Moreno, M.; Perez-Cañaveras, Rosa M.; De Raeve, Paul; Mikkonen, Kristina
Abstract: Background: The assessment of nursing students' nursing competence is a matter of concern worldwide and the complexity of assessing students' clinical competence has challenged educators for decades. It has been recognized that there is inconsistency among assessment methods and tools between countries and institutions. Objective: To identify the current best evidence on the assessment of nursing students' competence in clinical practice. Design: Systematic review of reviews. Data sources: The electronic databases CINAHL, PubMed, Eric, Medic and the JBI Database of Systematic Reviews and Implementation Reports were searched in autumn 2018. Review methods: Two researchers independently assessed the eligibility of the studies by title, abstract and full-text, and then assessed the methodological quality of the included studies. Analysis of study findings was conducted using the thematic synthesis approach. Results: Six reviews were included following critical appraisal. Assessment tools used to assess students' nursing competence commonly focus on the domains of professional attributes, ethical practices, communication and interpersonal relationships, nursing processes, critical thinking and reason. Clinical learning environments and mentoring provide important support structures and guide the learning of students. The availability of assessment tools and criteria along with providing individualized feedback and time for reflection strengthen the objectivity and reliability of assessment. Conclusions: There continues to be a need to develop consistent and systematic approaches in assessment, and to use reliable and valid instruments in assessment. Mentors find assessment of students' competence to be particularly challenging and emphasize the importance of clear assessment criteria, support from nurse educators and further education on assessment. Further development in feedback practices and providing students with opportunities for reflection are important in supporting the continuous learning process of students.